(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The scientific article is devoted to the study of the microelement composition of vegetation in the Tyup river basin of the Issyk-Kul region. 60 plant species were analyzed, covering almost the entire species composition of the main associations; plants of different types, life forms and ecological groups were presented. The publication provides thorough and detailed analyzes for the content of trace elements: Cu, Co, Mo, Mn, Pb, Sr, Sn and Ni. All analyzes were done at the Institute of Geochemistry and Analytical Chemistry named after. V.I.Vernadsky (Moscow), lab. Biogeochemistry and radioecology and the “Central Laboratory” under the Ministry of Natural Resources, Ecology and Technical Supervision of the Kyrgyz Republic using the method of atomic emission spectrometry.